Linear scaling between microbial predator and prey densities in the global ocean. (22nd November 2022) - Rajakaruna, Harshana; Omta, Anne Willem; Carr, Eric; Talmy, David
Abstract: It has been proposed that microbial predator and prey densities are related through sublinear power laws. We revisited previously published biomass and abundance data and fitted Power‐law Biomass Scaling Relationships (PBSRs) between marine microzooplankton predators ( Z ) and phytoplankton prey ( P ), and marine viral predators ( V ) and bacterial prey ( B ). We analysed them assuming an error structure given by Type II regression models which, in contrast to the conventional Type I regression model, accounts for errors in both the independent and the dependent variables. We found that the data support linear relationships, in contrast to the sublinear relationships reported by previous authors. The scaling exponent yields an expected value of 1 with some spread in different datasets that was well‐described with a Gaussian distribution. Our results suggest that the ratios Z / P, and V / B are on average invariant, in contrast to the hypothesis that they systematically decrease with increasing P and B, respectively, as previously thought.